Effect of Allelopathic Potential of Cabbage on Germination and Seedling growth of Three weeds (Journal of Humanitarian and Applied Sciences, 2023)
It was evident that final germination, plumule and radical lengths decreased significantly by increasing concentration of aqueous cabbage extracts. The same results obtained in laboratory experiments more or less agree with that obtained with field experiments. These results suggest that brassica residues are capable of delaying seedling emergence and reducing establishment of wild oat, wild mustard and nettle-leaved goosefoot wild grass. The results also demonstrated that, 8% cabbage root extract completely inhibit the germination of wild oat seeds. Meanwhile application of 6%, 4% and 2% aqueous cabbage root extract, yielding in 90%, 72% and 44% reduction in the germination of wild oat seeds respectively. Chenopodium seeds are sensitive to allelopathic effects of cabbage root aqueous extracts. Maximum reduction in germination occurred with 8% concentration. At concentrations of 6% and 4 %; the germination was reduced to about 62% and 47% respectively. However, 2% concentration resulting in reduction of 40% of chenopodium seeds germination. All of the above results were in comparison with that distilled water control. The current study indicated that, there was a negative linear regression between cabbage leave extract concentration and germination percentage for all three tested wild grasses seeds, Wild oat is the more sensitive to the allelopathic effect of cabbage leaves extracts, it reach to zero germination percentage at 6% concentration. and Wild Mustard reaches at 8% but Chenopodium reaches at 10.9% concentration, also illustrate the effect of cabbage leaves extracts on germination of wild mustard seeds. Zero germination percentage obtained when 8% aqueous cabbage leaves extract used. Mean while, the use of 6%, 4% and 2% cabbage leaves extract leads to 20%, 22% and 39% germination percentage respectively.
Keywords: Allelopathic; Germination